A typology of Roma misrepresentation in contemporary Europe: Marginalization, denizenship, suppression and co-option - Pier-Luc Dupont (Deusto Journal of Human Rights, 2025)
Building on David Theo Goldberg’s account of the racial state and empirical research on Roma people in Europe, this article delineates various ways in which racism can undermine political representation. To that end it deploys Nancy Fraser’s concepts of “ordinary-political misrepresentation” and “misframing”; the all-affected/subjected principle used to identify those entitled to influence political decisions; and Hannah Pitkin’s four-dimensional conception of representation as substantive, formal, descriptive and symbolic. The article distinguishes racialized forms of misrepresentation rooted in everyday discrimination and educational exclusion (marginalization), the denial of citizenship (denizenship), the negation of subjectively held cultural identities (suppression) and the capture of minority leaders (co-option). It suggests that the first constitutes an “ordinary-political” form of inequality among citizens, whereas the latter three violate the all-affected/subjected principle through the misframing of the legitimate policymaking constituency.